2009
DOI: 10.1056/nejmoa0905360
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Hedgehog Pathway in Advanced Basal-Cell Carcinoma

Abstract: GDC-0449, an orally active small molecule that targets the hedgehog pathway, appears to have antitumor activity in locally advanced or metastatic basal-cell carcinoma. (ClinicalTrials.gov number, NCT00607724.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
458
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 996 publications
(483 citation statements)
references
References 19 publications
12
458
0
1
Order By: Relevance
“…The adverse events that tended to be more prevalent among vismodegib-treated versus placebo-treated patients (i.e., vomiting, weight loss, decreased appetite, dehydration, muscle cramps, dysgeusia, and asthenia/fatigue), regardless of chemotherapy backbone, were primarily those previously reported in association with vismodegib (12). The frequent occurrence of low-grade toxicities associated with vismodegib, superimposed on toxicities associated with the FOLFOX-bevacizumab or FOLFIRI-bevacizumab treatment regimens, may have increased treatment discontinuation among vismodegibtreated patients.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The adverse events that tended to be more prevalent among vismodegib-treated versus placebo-treated patients (i.e., vomiting, weight loss, decreased appetite, dehydration, muscle cramps, dysgeusia, and asthenia/fatigue), regardless of chemotherapy backbone, were primarily those previously reported in association with vismodegib (12). The frequent occurrence of low-grade toxicities associated with vismodegib, superimposed on toxicities associated with the FOLFOX-bevacizumab or FOLFIRI-bevacizumab treatment regimens, may have increased treatment discontinuation among vismodegibtreated patients.…”
Section: Discussionmentioning
confidence: 76%
“…In vismodegib-treated patients, levels of vismodegib (12), oxaliplatin (20,21), irinotecan (22), 5-FU (19,23), and bevacizumab (24) were within the expected ranges for the doses administered ( Supplementary Figs. SA1-SA5).…”
Section: Pharmacokineticsmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent clinical trial revealed that GDC-0449, an orally active small molecule that targets the hedgehog pathway, appears to have antitumor activity in locally advanced or metastatic basal cell carcinoma (Von Hoff et al 2009). …”
mentioning
confidence: 99%
“…The Hedgehog pathway has been implicated in the development of basal cell carcinoma (BCC) and other cancers 1, 2, 3, 4, 5, 6, 7, 8, 9. Vismodegib is well tolerated in clinical practice, with pharmacodynamic evidence of Hedgehog pathway inhibition via GLI1 suppression and tumor regression in BCC patients and medulloblastoma 10, 11, 12. Vismodegib was approved by the US Food and Drug Administration (FDA) in January, 2012, for the treatment of adults with metastatic BCC or with locally advanced BCC 13, 14…”
mentioning
confidence: 99%